Insel Im Krieg
Life in Mrkopalj village in Istra depicted, where Croats and Serbs live peacefully together despite the raging war. Also depicted is Jasenak village where the Serbian majority lives with Croatian refugees from Eastern Slavonia. Interviews with the refugees and village inhabitants.